Cation disorder and thermoelectric properties in layered ternary compounds MBi2Te4 (M = Ge, Sn). Issue 3 (10th January 2022) - Zhang, Hu; Lu, Lu; Mi, Shaobo
Abstract : Atomic-scale investigation of layered thermoelectric materials reveals the positional disordering of heterovalent cations (Ge +2 /Bi +3 and Sn +2 /Bi +3 ) in the crystal lattice (the 3 a Wyckoff site) of ternary MBi2 Te4 (M = Ge, Sn) compounds. Abstract : Atomic-scale understanding of the microstructural properties of thermoelectric (TE) materials is critical for exploring the structure–property relationship and enhancing the macroscopic performance of TE materials. Here, we demonstrate direct evidence of cation disorder in the layered compounds MBi2 Te4 (M = Ge, Sn) by using scanning transmission electron microscopy imaging. The positional disordering of heterovalent cations (Ge +2 /Bi +3 and Sn +2 /Bi +3 ) mainly occurs in the 3 a Wyckoff site in the crystal lattice of MBi2 Te4 (M = Ge, Sn), which can affect the phonon propagation and reduce lattice thermal conductivity in these compounds. Both cation disordered GeBi2 Te4 and SnBi2 Te4 are degenerate n-type semiconductors with the highest thermoelectric figure of merit of ∼0.15 and ∼0.013 at 400 K, respectively. Our findings with MBi2 Te4 (M = Ge, Sn) are believed to be helpful in understanding the cation ordering in the layered ternary TE compounds, which provides a strategy to tune the electron and thermal transport properties in the TE materials by incorporating deficiency or excess of constituent elements into the layered TE materials.